Association of SNP g.232 G>T Calpain Gene with Growth and Live Meat Quality Prediction using Ultrasound Images in Bali Cattle - Dairoh Dairoh; Jakaria Jakaria; Mokhamad Fakhrul Ulum; Andi Baso Lompengeng Ishak; Cece Sumantri (Indonesian Center for Animal Research and Development (ICARD), 2021)
Bali cattle (Bos javanicus) are native Indonesian cattle, domesticated from banteng (Bibos banteng). Genes that have an important role in meat quality are calcium-activated neutral protease genes, known as calpains (CAPN). The objective of this study was to evaluate the polymophisms of calpain gene SNP g.232 G>T by PCR-RFLP technique and its influence on growth trait and meat quality of Bali cattle detected by ultrasound imaging of longissimus dorsi thickness (LDT), back fat thickness (BFT), marbling score (MS), and intramuscular fat percentage (PIMF). The polymorphisms of CAPN1 gene were analyzed by PCR-RFLP using BglII restriction enzyme (n=52 cattle). The ultrasound images of longissimus dorsi muscle were carried out transversally and longitudinal between 12th -13th thoracic vertebrae then analyzed by Image-J NIH software. Result showed that SNP g.232 G>T of CAPN1 gene was polymorphic in Bali cattle. SNP g.232 G>T of CAPN1 gene in Bali cattle has higher diversity which was showed of 0.48 heterozygosity value and was in Hardy-Weinberg equilibrium. The polymorphisms of SNP g.232 G>T was associated significantly (P<0.05) with bodyweight at 730 days, marbling score (MS), and intramuscular fat percentage (PIMF). It suggests that the CAPN1 gene in Bali cattle is a candidate for Marker Assisted Selection (MAS), which influences body weight at 730 days, marbling score, and percentage of intramuscular fat.